Application of OVT Domain Processing Technology in 3D Seismic Exploration of Coalbed Methane in Heshun Hengling Block - Yao, Zhicheng (International Journal of Natural Resources and Environmental Studies, 2024)
This study introduces the OVT (Offset Vector Tile) domain processing technology to improve the accuracy of small structure detection in 3D seismic exploration of coalbed methane in the Heshun-Hengling block in China. The OVT technology optimizes wide azimuth seismic data processing through steps such as facet division, five-dimensional regularization, pre-stack time migration, and azimuthal anisotropy correction. The results show that OVT processing retains azimuth information, enhancing the ability to reflect stratum changes with azimuth; azimuthal anisotropy correction improves the resolution of the profile. The profile after OVT processing has a natural waveform, good continuity of the phase axis, and a wide frequency band, meeting the requirements of the “Coalbed Methane Seismic Exploration Specification”. It demonstrates the advantages of OVT technology in imaging complex geological structures, providing a new perspective for seismic exploration.